2010
DOI: 10.1073/pnas.0912943107
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic trafficking of γδ T cells to skin is dependent on E/P selectin ligands and CCR4

Abstract: Dendritic epidermal T cells (DETC) express an invariant Vγ3/Vδ1 T-cell receptor, appear in fetal epidermis, and form a population of resident epidermal T cells. Their temporal development in the thymus has been studied extensively. However, little is known about the mechanisms involved in the embryonic trafficking of DETC from thymus to epidermis. We demonstrate that DETC in adult skin, as well as the DETC precursors in fetal thymus, express E and P selectin ligands (E-and P-lig). Mice deficient in α1,3 fucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
2
61
1
Order By: Relevance
“…Dermal γδ T cells have T effector memory phenotype (CD44 hi CD62L – ) and express the skin homing molecules --- E- and P-lig. Our previous studies had demonstrated that embryonic trafficking of DETC to skin is dependent on E-lig and CCR4 [21]. Interestingly, the majority of dermal γδ T cells also express CD69 and CD103 (S1B Fig), two molecules typically expressed by tissue resident memory T cells (T RM ) [20, 2224].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermal γδ T cells have T effector memory phenotype (CD44 hi CD62L – ) and express the skin homing molecules --- E- and P-lig. Our previous studies had demonstrated that embryonic trafficking of DETC to skin is dependent on E-lig and CCR4 [21]. Interestingly, the majority of dermal γδ T cells also express CD69 and CD103 (S1B Fig), two molecules typically expressed by tissue resident memory T cells (T RM ) [20, 2224].…”
Section: Resultsmentioning
confidence: 99%
“…Epidermis and dermis sheets were separated as previously described [21]. Briefly, ears were split into dorsal and ventral halves.…”
Section: Methodsmentioning
confidence: 99%
“…Vg3/d1 T cells destined for the skin are generated and selected exclusively in the fetal thymus between embryonic days 15 and 18 (7,(21)(22)(23), and then migrate to the skin in an E/P selectindependent fashion (24), where they remain for life. In Vd 2/2 mice, ab TCR + DETC seed the skin, but disappear with time (17), suggesting that the epidermal niche for T cells cannot be successfully occupied by conventional T cells.…”
mentioning
confidence: 99%
“…The upregulation of a few key receptors on thymic Vγ3 + γδ T cells is critical for their epidermis homing (e.g., CCR10 and S1P1) and maintenance (e.g., CCR4) (Jiang et al, 2010; Jin et al, 2010; Nakamura et al, 2013; Xiong et al, 2004). Thus, we further examined the expression of these DETC homing/maintenance-associated molecules.…”
Section: To the Editormentioning
confidence: 99%